Trends and inequalities in the nutritional status of adolescent girls and adult women in sub-Saharan Africa since 2000: a cross-sectional series study - Serge M A Somda; Abdoulaye Maïga; Safia S Jiwani; Cheikh Mbacké Faye; Shelley Walton; Tome Ca; Richard Kumapley; Giovanna Gatica-Domínguez; Elizabeth Hazel; Inacio Crochemore-Silva; Barbara Baille; Sujata Bose; et al. (BMJ Global Health)
Introduction Evidence on the rate at which the double burden of malnutrition unfolds is limited. We quantified trends and inequalities in the nutritional status of adolescent girls and adult women in sub-Saharan Africa.Methods We analysed 102 Demographic and Health Surveys between 1993 and 2017 from 35 countries. We assessed regional trends through cross-sectional series analyses and ran multilevel linear regression models to estimate the average annual rate of change (AARC) in the prevalence of underweight, anaemia, anaemia during pregnancy, overweight and obesity among women by their age, residence, wealth and education levels. We quantified current absolute inequalities in these indicators and wealth-inequality trends.Results There was a modest decline in underweight prevalence (AARC=−0.14 percentage points (pp), 95% CI −0.17 to -0.11). Anaemia declined fastest among adult women and the richest pregnant women with an AARC of −0.67 pp (95% CI −1.06 to -0.28) and −0.97 pp (95% CI −1.60 to -0.34), respectively, although it affects all women with no marked disparities. Overweight is increasing rapidly among adult women and women with no education. Capital city residents had a threefold more rapid rise in obesity (AARC=0.47 pp, 95% CI 0.39, 0.55), compared with their rural counterparts. Absolute inequalities suggest that Ethiopia and South Africa have the largest gap in underweight (15.4 pp) and obesity (28.5 pp) respectively, between adult and adolescent women. Regional wealth inequalities in obesity are widening by 0.34 pp annually.Conclusion Underweight persists, while overweight and obesity are rising among adult women, the rich and capital city residents. Adolescent girls do not present adverse nutritional outcomes except anaemia, remaining high among all women. Multifaceted responses with an equity lens are needed to ensure no woman is left behind.